Tangled Relationships : Boundary Issues and Dual Relationships in the Human Services - Reamer, Frederic (Foundations of Social Work Knowledge Series, 2001)
Should a therapist counsel a former lover or accept a client's gift? If so, has a boundary been crossed? Some boundary issues, like beginning a sexual relationship with a client, are obvious pitfalls to avoid, but what about more subtle issues, like hugging a client or disclosing personal information to a client? What are the boundaries of maintaining a friendship with a former client or the relative of a client? When do conflicts of interest overburden the client-practitioner relationship?Frederic Reamer, a leading authority on professional ethics, offers a definitive and up-to-date analysis of boundary issues, a rapidly emerging topic in the field of human services. One of the only works in the field to provide a conceptual framework for the dual relationship between practitioner and client, this book provides an in-depth look at the complex forms these relationships take. It also gives practical risk-management models to aid human service professionals in the prevention of problematic situations and the managing of dual relationships. Reamer examines the ethics involving intimate and sexual relationships with clients and former clients, practitioners' self-disclosure, giving and receiving favors and gifts, bartering for services, and unavoidable and unanticipated circumstances such as social encounters and geographical proximity. Case vignettes that help illustrate important points are also included in each chapter.